TV Series and Social Media: Powerful Engagement Factors in Mobile Video Games - Saez, Yago; Mochón, Asunción; Rada, Fernando (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2022)
The free-to-play business model has become hegemonic in the mobile video game industry, displacing the traditional paid content model that was the norm until the appearance of manufacturers’ app stores. Companies attempt to monetize these games by means of in-game micro-transactions and in-game advertising; thus, it is essential to acquire an enormous number of users because only a small percentage will ultimately make any purchases. To keep players engaged, companies typically put in place marketing and design strategies derived from behavioral telemetry, to maintain a grip on players. We propose an innovative approach, focusing our attention on the impact of having a video game based on a famous TV series. Furthermore, we analyze the effect of social networks on game metrics. The outcome indicates that developing a game based on a TV series and integrating social media with the gameplay improve and reinforce the user’s activation, retention and monetization.
Keywords: videogame; games; social network; free-to-play; monetization; customer retention; character identification; tv series; digital marketing; IJIMAI